2019
DOI: 10.3390/pr7110779
|View full text |Cite
|
Sign up to set email alerts
|

Taste Masking of Nizatidine Using Ion-Exchange Resins

Abstract: The purpose of this study was to mask the bitter taste of nizatidine (NZD) using cation-exchange resins. Amberlite IRP-69 and Dowex-50 containing cross-linked polystyrene backbones were used. The drug resin complexes were prepared by batch process using drug: resin ratios of 1:1, 1:3, and 1:5. The optimum drug: resin ratio and the time required for maximum percentage drug loading into the complexes were determined. The selected drug-resin complexes were evaluated for morphology, drug release, and taste. The NZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The nizatidine showed high complexation efficiency in a stoichiometric ratio of 1:3 (drug:resin) with Dowex-50 because of like-charged ions, the H + compared to Amberlite IRP-69 with Na + ions. The dissolution studies exhibited the complete release within 1 h. The in vivo taste masking studies reported a pleasant taste for the DRC [115].…”
Section: Drug-resin Complexes (Drc)mentioning
confidence: 85%
“…The nizatidine showed high complexation efficiency in a stoichiometric ratio of 1:3 (drug:resin) with Dowex-50 because of like-charged ions, the H + compared to Amberlite IRP-69 with Na + ions. The dissolution studies exhibited the complete release within 1 h. The in vivo taste masking studies reported a pleasant taste for the DRC [115].…”
Section: Drug-resin Complexes (Drc)mentioning
confidence: 85%
“…Patients report feeling satisfied with their treatment after using this tried-and-true dose form, which features improved absorption. [38][39] It was observed that, out of the three resins that were put to the test, Indion 204 had the best results when combined with a ratio of 1:1.5, which made it possible for the most complexation to take place after only four hours of stirring. The resinate is processed into granules, which are characterised by adequate levels of angle of repose, bulk density, and flow property respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The powders or microspheres considered for this review (Table S1) were mainly prepared through spray drying. In these cases, the bitter-tasting drug was formulated with taste-masking polymers, such as various types of Eudragit ® [57,80], two types of Kollicoat ® [81] or carrageenan [82], cellulose derivates [83], or cation-exchange resins [84]. In one study, taste masking was achieved by using nanoemulsions of different oils.…”
Section: Powders Microspheres and Granulesmentioning
confidence: 99%
“…Samples for e-tongue measurements were typically prepared as follows: the powders were dissolved in from 5 to 100 mL of water or artificial saliva buffer solution for a duration of from 30 to 300 s [56,57,84,87]. A filtration step was then performed using 0.45 µm membrane filters to remove insoluble components or any remaining particles, ensuring a particle-free solution [57,84] (Figure 4).…”
Section: Powders Microspheres and Granulesmentioning
confidence: 99%